The Effect of Garcinia Mangostana Linn Extract to The Levels of Circulating Endothelial Cells and Endothelial Progenitor Cells in Patients with High Framingham Score - Aditha Satria Maulana; Djanggan Sargowo; Ardian Rizal; Heny Martini; Mohammad Saifur Rohman; Anna Fuji Rahimah; Jonny Karunia Fajar (Universitas Brawijaya, 2020)
Background : Recently, studies have concerned on the use of xanthones for treating patients with cardiovascular diseases. In our country, xanthones were found in Garcinia Mangostana Linn.Objectives : To assess the effect of Garcinia Mangostana Linn Extract (GMLE) to the levels of Circulating Endothelial Cells (CEC) and Endothelial Progenitor Cells (EPC) in patients with high framingham score.Methods : A prospective cohort study was conducted from November 2018 to January 2019. The patients were divided into two groups. The first group was given 2520 mg/day of GMLE for 90 days and the second group was given placebo. In sub group analyses, patients were divided based on previous medication, including statin, statin and angiotensin-converting-enzyme inhibitors (ACEI) or angiotensin II receptor blockers (ARB), statin and oral antidiabetic drugs (OAD), and statin and ACEI or ARB and OAD. The outcome measures were CEC and EPC levels, measured at baseline and after 90 days of treatment. We used multiple linear regression to analyze the correlation and effect estimates.Results: A total of 72 patients was included in our study. All of the patients baseline characteristics were distributed homogeneously (p>0.05). Our findings confirmed that GMLE administration was associated with decreased CEC level compared to placebo. On other hands, increased EPC level compared to placebo was observed after GMLE administration. In sub-group analyses, our study found that the combination of GMLE with statin and ACEI or ARB and the combination of GMLE with statin and ACEI or ARB and OAD were associated with decreased level of CEC compared to placebo, with the odd ratios were 0.12 and 0.18, respectively. Conversely, increased level of EPC was observed in subjects receiving the combination of GMLE with statin and ACEI or ARB and the combination of GMLE with statin.Conclusion: Administration of GMLE as adjuvant therapy is associated with the improvement of CEC and EPC levels in patients with high framingham scores.